Strategi Pemasaran Digital Agribisnis Kopi Robusta (Coffea canephora) Sebagai Upaya Peningkatan Pendapatan Petani Kopi di Kabupaten Tulungagung - Lestari, Mufida Diah; Sajali, Chusnatul Ulaela; Solikah, Umi Nur (Journal of Agribusiness, Social and Economic, 2025)
Robusta coffee (Coffea canephora) is one of the leading commodities in Tulungagung Regency that has great potential to be developed through an agribusiness approach. However, limited market access and low product competitiveness are the main challenges for coffee farmers in increasing their income. This study aims to formulate an effective digital marketing strategy in supporting robusta coffee agribusiness and analyse its impact on increasing farmers' income. The method used was a descriptive qualitative and quantitative approach through surveys, in-depth interviews, and SWOT analysis of local coffee agribusiness actors, including farmer cooperatives and coffee processing MSMEs. The results show that the utilisation of social media, e-commerce, and other digital platforms can expand market reach, increase product added value, and strengthen the branding of Tulungagung robusta coffee. Digital strategies integrated with strengthening farmers' capacity in information technology have proven effective in increasing sales volume and farmers' income. Therefore, digital marketing is a relevant strategic step to strengthen the competitiveness of robusta coffee agribusiness in the digital economy era.